The analytical characteristic of development of housing market of Kiev - Sorokina, L.; Goyko, A. (Ways to Improve Construction Efficiency, 2015)
In article the technique of forecasting of the offers’ price of apartments in primary market of real estate of Kiev developed on the basis of results of the regression analysis with use of such elements of fuzzy arithmetics as the fuzzy linear algebraic equations is offered. This methodical providing gives the chance mоrе of flexible forecasting of changes of market balance and the offer in primary market of residential real estate.